Poster Interaktif 'Wali Songo dan Budaya Islam Nusantara' Sebagai Media Pembelajaran PAI untuk Siswa Kelas IV Sekolah Dasar - Sava Tifani; Aulia Holilah; Ginasti Aprillia; Ani Nur Aeni (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2022)
Walisongo has an important role in the spread of Islam in Nusantara, especially on the island of Java. The Walisongo material contained in the basic competencies of Islamic religious education lessons in grade IV elementary school is the right step to introduce the Islamic side of the archipelago to grade IV elementary school students. In material related to Islamic culture and history, students are often considered as boring material because it is usually only presented through conventional learning media, for example with text in material books. Therefore, appropriate and interesting learning media products need to be presented in PAI learning, especially in this material so that later the student's paradigm of the material can change. The method used in this study is the D&D research method to test the products presented. The presentation of learning media products in the form of interactive posters is believed to be able to help students to increase learning motivation and actually involve students to follow the commendable attitude of Walisongo. Through this interactive poster, it is able to arouse students' learning motivation according to research conducted on fourth grade students of SDN 1 Ibun, the poster presented can help children recognize the characteristics of the Islamic culture of Nusantara go brought by Walisongo, assist children in applying Walisongo's exemplary values, and help teachers in the learning process on related materials.